Pelatihan Model Pembelajaran IPA Terpadu untuk Profesionalisme Guru SMP Se-Kabupaten Pesawaran - Berti Yolida; Dewi Lengkana; Rini Rita T. Marpaung; Dina Maulina; Ismi Rakhmawati; Median Agus Priadi; M. Coesamin (Nuwo Abdimas, 2023)
Science subjects in junior high school contain concepts from three different disciplines, namely Biology, Physics, and Chemistry, so that these subjects are taught by three different teachers. Even though the concept of science should not be compartmentalized, but must be able to complement one another. Likewise with the skills that must be taught in accordance with the demands of Basic Competence in the curriculum. The purpose of this service activity is to increase teacher professionalism, especially in teaching aspects, especially science subjects. The target for the training is science teachers at junior high schools in Pesawaran district. There are several training methods used, namely: need assessment, information discussion, assignment method, workshops on making integrated science lesson plans, presentations, discussions and information exploration, peer teaching at the MGMP. Improvement data was measured using a questionnaire instrument, essay test questions, the Teacher Performance Analysis test instrument (APKG) given before and after treatment, and peer teaching observation sheets (with MGMP). Data on increasing professionalism will be analyzed descriptively and using the t-test. The conclusions of the implementation of the integrated science learning model implementation training are: 1) The integrated science learning model implementation training is capable of increasing teacher professionalism in the aspects of knowledge, aspects of personality and social aspects. And the highest increase occurred in the social and personality aspects. 2) Increasing the ability to make an integrated RPP IPA less significant.